Secondary surgical management of suprachoroidal hemorrhage during pars plana vitrectomy - Vuković, Dragan Rajko; Petrović, Sanja M; Paović, Predrag D (Vojnosanitetski pregled, 2015)
Introduction. Suprachoroidal hemorrhage (SCH) is one of the most feared and devastating complications of intraocular surgery. Intraoperative SCH is defined as sudden hemorrhagic swelling of the choroid which develops at time of intraocular surgery, and is associated with expulsion of some or all of the intraocular contents. Case report. A 56-year-old man was admitted to our Clinic with bullose retinal detachment in the left eye. Intraoperatively, during the substitution of perfluorocarbone liquid (PFCL) with silicone oil, which is very rare situation, a sudden loss of red reflex happened and SCH was recognized as the cause. No attempt was made to drain the suprachoroidal blood. After 3 weeks the patient was scheduled for pars plana vitrectomy. Initial drainage of liqufied blood was made through a sclerotomy port during pars plana inferotemporally. Massive epiretinal proliferation with funnel shaped retinal detachment was solved during vitrectomy and internal tamponade with silicone oil was done. Postoperative visual aquity was 2/60 on the third postoperative day. Conclusion. Although suprachoroidal hemorrhage is one of most feared and devastating complications of intraocular surgery, it might have relatively good prognosis with proper preoperative, intraoperative and postoperative management.
Keywords: vitrectomy; eye hemorrhage; intraoperative complications; risk factors